2013
DOI: 10.5897/ajmr12.390
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria found on banks automated teller machines (ATMs)

Abstract: Increasing number of people have used automated teller machines (ATMs) by years, but we know less about their bacterial colonization status. For this purpose, we performed bacterial swab cultures from a total of 100 ATM devices in our city. All devices were found positive for Bacillus spp., and coagulase negative staphylococci (CNS) were isolated from nine devices, including one methicillin resistant strain. Staphyloccocus aureus grew in two devices, where one of them was identified as methicillin resistant (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…With a few exceptions, the analysed ATMs were not highly contaminated, compared with some others studies. Tekerekoğlu et al [32] found higher values of contamination on ATMs in Turkey with CNS between 1.5 × 10 3 -1.2 × 10 4 CFU/mL and E. coli between 10 3 -10 4 CFU/mL. Saroja et al [9], in India, showed a total microbial load ranging from 4.0 × 10°to 1.9 × 10 5 CFU/mL and presence of E. coli and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions, the analysed ATMs were not highly contaminated, compared with some others studies. Tekerekoğlu et al [32] found higher values of contamination on ATMs in Turkey with CNS between 1.5 × 10 3 -1.2 × 10 4 CFU/mL and E. coli between 10 3 -10 4 CFU/mL. Saroja et al [9], in India, showed a total microbial load ranging from 4.0 × 10°to 1.9 × 10 5 CFU/mL and presence of E. coli and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The method adopted by Mehmet et al (2013) were used to characterize and describe the pure isolates obtained in this study. The cultural characteristics were observed and morphological characterization was ascertained after Gram staining followed by microscopy.…”
Section: Bajopas Volume 13 Number 1 June 2020mentioning
confidence: 99%
“…Bacterial isolates were characterized as described by Mehmet et al, (2013) using colonial, microscopic and biochemical characteristics. All tests were done using standard basic media and reagents (Atlas, 1997).…”
Section: Characterization and Identification Of Bacterial Isolatesmentioning
confidence: 99%